2022
DOI: 10.3390/ijms23179567
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Therapeutic Potential of Ectoine in Duchenne Muscular Dystrophy: Comparison with Taurine, a Supplement with Known Beneficial Effects in the mdx Mouse

Abstract: Duchenne Muscular Dystrophy (DMD) is a debilitating muscle disorder that condemns patients to year-long dependency on glucocorticoids. Chronic glucocorticoid use elicits many unfavourable side-effects without offering satisfying clinical improvement, thus, the search for alternative treatments to alleviate muscle inflammation persists. Taurine, an osmolyte with anti-inflammatory effects, mitigated pathological features in the mdx mouse model for DMD but interfered with murine development. In this study, ectoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…To study the possibility of ectoineinduced tumors in HaCaT keratinocytes, we treated cells with ectoine for 30 weeks and xenografted them into athymic nude mice. This experiment was modified from the previous studies [69,70]. Approximately 5 × 10 6 HaCaT cells treated with ectoine for 24 weeks were subcutaneously injected into the dorsal flank of athymic nude mice.…”
Section: Tumorigenicity In Vivo Experimentsmentioning
confidence: 99%
“…To study the possibility of ectoineinduced tumors in HaCaT keratinocytes, we treated cells with ectoine for 30 weeks and xenografted them into athymic nude mice. This experiment was modified from the previous studies [69,70]. Approximately 5 × 10 6 HaCaT cells treated with ectoine for 24 weeks were subcutaneously injected into the dorsal flank of athymic nude mice.…”
Section: Tumorigenicity In Vivo Experimentsmentioning
confidence: 99%
“…To study the possibility of ectoine-induced tumors in HaCaT keratinocytes, we treated cells with ectoine for 30 weeks and xenografted them into athymic nude mice. This experiment was modified from the previous studies [38,39]. Approximately 5 × 106 HaCaT cells treated with ectoine for 24 weeks were subcutaneously injected into the dorsal flank of athymic nude mice.…”
Section: Tumorigenicity In Vivo Experimentsmentioning
confidence: 99%
“…In this respect, the use of taurine has been most widely studied and beneficial effects have been observed in mouse models, however, interference with murine development has also surfaced [23], warranting the exploration of alternative compounds. In an earlier study we were the first to study ectoine in the MDX and reported improved skeletal muscle histopathology and anti-inflammatory effects [24]. Ectoine is a natural compound found in extremophiles [25].…”
Section: Introductionmentioning
confidence: 99%